2019
DOI: 10.1073/pnas.1810491116
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between differentially expressed enzymes contributes to light color acclimation in marine Synechococcus

Abstract: MarineSynechococcus, a globally important group of cyanobacteria, thrives in various light niches in part due to its varied photosynthetic light-harvesting pigments. ManySynechococcusstrains use a process known as chromatic acclimation to optimize the ratio of two chromophores, green-light–absorbing phycoerythrobilin (PEB) and blue-light–absorbing phycourobilin (PUB), within their light-harvesting complexes. A full mechanistic understanding of howSynechococcuscells tune their PEB to PUB ratio during chromatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 31 publications
2
52
0
Order By: Relevance
“…Although MpeV is not directly involved in CA4 since CpeB and MpeB do not change chromophorylation between blue and green light [27], it is worth noting that this enzyme forms a well-defined subfamily that is specifically found in CA4-A strains, one of the two Synechococcus CA types (with CA4-B), while its paralog MpeU is found in a much larger set of pigment types, encompassing both CA4 types as well as the two known blue light specialists (3c and 3f; Figure 3). MpeU is also a lyase-isomerase, but its substrate specificity remains unknown [38]. Advances made in the present study about the necessity of coexpressing cpeS and cpeZ with the lyase to be characterized may help unveil MpeU substrate specificity in the near future.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although MpeV is not directly involved in CA4 since CpeB and MpeB do not change chromophorylation between blue and green light [27], it is worth noting that this enzyme forms a well-defined subfamily that is specifically found in CA4-A strains, one of the two Synechococcus CA types (with CA4-B), while its paralog MpeU is found in a much larger set of pigment types, encompassing both CA4 types as well as the two known blue light specialists (3c and 3f; Figure 3). MpeU is also a lyase-isomerase, but its substrate specificity remains unknown [38]. Advances made in the present study about the necessity of coexpressing cpeS and cpeZ with the lyase to be characterized may help unveil MpeU substrate specificity in the near future.…”
Section: Discussionmentioning
confidence: 86%
“…The marine Synechococcus sp. strain RS9916 possesses the ability to alter the ratio of the blue-light-absorbing chromophore phycourobilin (PUB) [absorbance maximum (λ max ) ∼495 nm] and the green-light-absorbing chromophore phycoerythrobilin (PEB) (λ max ∼545 nm) on the distal portion of the PBS rods, a phenomenon known as type IV chromatic acclimation (CA4) ( 3 , 6 , 35 , 36 , 37 , 38 , 39 ). During CA4, the PUB-to-PEB ratio (PUB:PEB) is adjusted to be higher in blue light and lower in green light in order to optimize light capture in changing light color environments ( 3 , 31 , 35 , 36 , 39 , 40 ).…”
mentioning
confidence: 99%
“…Surprisingly, some Synechococcus populations inhabiting the vast iron-poor areas of the Pacific Ocean that had been genetically assigned to the CA4-A group were found to possess mpeZ, encoding a PEB lyase-isomerase, but lacked fciA and fciB, which encode the master regulators of CA4. Also missing was mpeY, encoding a PEB lyase (101). The phenotype of such cells would be that of a blue light specialist, a conclusion confirmed by the finding of an identical genomic arrangement in BIOS-E4-1, a strain isolated from iron-poor waters of the southern Pacific Ocean, which exhibits a blue light specialist phenotype.…”
Section: Molecular Characterization Of the Genes And Proteins Involvementioning
confidence: 81%
“…MpeZ was shown to be a PEB lyase-isomerase, attaching PEB to MpeA-C83 and isomerizing it to PUB (107). In a mpeZ mutant, PEB is attached to MpeA-C83 in blue light, and subsequent work has shown that the lyase MpeY is responsible for this attachment (101). In wild-type cells, RNA-seq data showed that although mpeY RNA levels are not regulated by CA4, in green light they are higher than mpeZ RNA levels, while in blue light, CA4 drives the mpeZ RNA level above mpeY.…”
Section: Molecular Characterization Of the Genes And Proteins Involvementioning
confidence: 99%
“…The spectra are normalized with respect to (a) the PEB peak at ~540 nm, and (b) the Chl-a peak at 440 nm. Spectra in (a) were measured in this study using methods described in Sanfilippo et al66 , whereas spectra in (b) are from Stomp et al31 . For comparison, grey peaks and valleys in the background show simulated underwater irradiance spectra and vertical dashed lines indicate the harmonics of the water molecule.…”
mentioning
confidence: 99%